A Quality Management Approach to Implementing Point-of-Care Technologies for HIV Diagnosis and Monitoring in Sub-Saharan Africa - Joseph P. Shott; Ronald M. Galiwango; Steven J. Reynolds (Journal of Tropical Medicine)
Technology advances in rapid diagnosis and clinical monitoring of human immunodeficiency virus (HIV) infection have been made in recent years, greatly benefiting those at risk of HIV infection, those needing care and treatment, and those on antiretroviral (ART) therapy in sub-Saharan Africa. However, resource-limited, geographically remote, and harsh climate regions lack uniform access to these technologies. HIV rapid diagnostic tests (RDTs) and monitoring tools, such as those for CD4 counts, as well as tests for coinfections, are being developed and have great promise in these settings to aid in patient care. Here we explore the advances in point-of-care (POC) technology in the era where portable devices are bringing the laboratory to the patient. Quality management approaches will be imperative for the successful implementation of POC testing in endemic settings to improve patient care.